An Intervention to Reduce Alcohol Consumption in Undergraduate Students Using Implementation Intentions and Mental Simulations: A Cross-National Study - Hagger, Martin; Lonsdale, A.; Koka, A.; Hein, V.; Pasi, H.; Lintunen, T.; Chatzisarantis, N. (Springer New York LLC, 2012)
Background: Excessive alcohol consumption has been linked to deleterious health consequences among undergraduate students. There is a need to develop theory-based and cost-effective brief interventions to attenuate alcohol consumption in this population. Purpose: The present study tested the effectiveness of an integrated theory-based intervention in reducing undergraduates' alcohol consumption in excess of guideline limits in national samples from Estonia, Finland, and the UK. Method: A 2 (volitional: implementation intention vs. no implementation intention) × 2 (motivation: mental simulation vs. no mental simulation) × 3 (nationality: Estonia vs. Finland vs. UK) randomized-controlled design was adopted. Participants completed baseline psychological measures and self-reported number of alcohol units consumed and binge-drinking frequency followed by the intervention manipulation. One month later, participants completed follow-up measures of the psychological variables and alcohol consumption.Results: Results revealed main effects for implementation intention and nationality on units of alcohol consumed at follow-up and an implementation intention × nationality interaction. Alcohol consumption was significantly reduced in the implementation intention condition for the Estonian and UK samples. There was a significant main effect for nationality and an implementation intention × nationality interaction on binge-drinking frequency. Follow-up tests revealed significant reductions in binge-drinking occasions in the implementation intention group for the UK sample only. Conclusion: Results support the implementation intention component of the intervention in reducing alcohol drinking in excess of guideline limits among Estonian and UK undergraduates. There was no support for the motivational intervention or the interaction between the strategies. Results are discussed with respect to intervention design based on motivational and volitional approaches.